PENGARUH GAYA HIDUP DAN PENDAPATAN TERHADAP KEPUTUSAN PEMBELIAN STARBUCKS COFFEE DI CENTER POINT MEDAN - Darma Manalu; Johanna Roshinta (Jurnal Ilmu Sosial Dan Politik, 2021)
This study aims to determine the effect of lifestyle and income on purchasing decisions for Starbucks Coffee at Center Point Medan, either partially or simultaneously. This study uses a quantitative approach with a causal associative method. The population in this research are all Starbucks Coffee Center Point buyers whose exact number is not known. Sampling using the Lemeshow formula amounted to 96 people. Data collection was done by using a questionnaire. The results of this study indicate that there is a positive and significant influence on lifestyle variables on purchasing decisions for Starbucks Coffee at Center Point Medan. It can be seen from the test results obtained a significant value of 0.000 <0.05 or t count 3.146 > t table 1.661. There is a positive and significant influence on the income variable on the purchasing decision of Starbucks Coffee at Center Point Medan. It can be seen from the test results obtained a significant value of 0.000 <0.05 or t count 5.718 > t table 1.661. And there is a simultaneous positive and significant effect on lifestyle and income variables on purchasing decisions for Starbucks Coffee at Center Point Medan. It can be seen from the test results obtained that the significant value of X1 and X2 is 0.000 <0.05 and the calculated F value is 83.605 > F table 3.09. While the value of the coefficient of determination (R) of 0.635 indicates that the purchasing decision variable can be explained by the lifestyle and income variables of 63.5%. While the remaining 36.5% is explained by other variables such as price variables, brand image, etc. It is recommended that Starbucks Center Point Medan should maintain the quality of coffee that is already well known and its facilities are good in accordance with the lifestyle and income of Starbucks customers.